Welcome Insight into Buddhist Vegetarianism in Sri Lanka: Review of James Stewart, Vegetarianism and Animal Ethics in Contemporary Buddhism - Barstow, Geoffrey (Humanimalia, 2016)
James Stewart, Vegetarianism and Animal Ethics in Contemporary Buddhism. London: Routledge, 2015. 214 pp. 145 hc.